The Role of the Family in Fostering Adolescent Religious Attitudes during the Covid-19 Pandemic - Ali Imran (State Islamic Institute of Palopo, 2022)
This study discusses the role of the family in fostering adolescent religious attitudes during the Covid 19 pandemic in North Kanna Village, Basse Sangtempe District, Luwu Regency. This study aims to determine the religious attitudes of adolescents, the role and strategies of families towards fostering religious attitudes, and family barriers in fostering adolescent religious attitudes during the COVID-19 pandemic in North Kanna Village, Basse Sangtempe District, Luwu Regency. This research is qualitative research using a descriptive approach. The subjects and objects of the study consisted of families/parents, adolescents aged 16-18 years, community leaders, religious leaders, and village heads. The data processing and data analysis techniques used data collection, data reduction, data presentation, and conclusion drawing, namely: 1 ). The religious attitudes of adolescents in North Kanna Village believe in succession, believing with awareness, religious doubts, and disobeying in worship. 2). The roles and strategies of parents in fostering adolescent religious attitudes in North Kanna Village include educators, supervisors, and role models as motivators. 3). Family barriers to fostering adolescent religious attitudes in North Kanna Village are the parents' common understanding of religion, lack of time, and the development of telecommunication media. The results of this study indicate that the role of the family on the religious attitudes of adolescents during the covid-19 pandemic: Parents must understand religious knowledge well about obligations and responsibilities to children in Islam, and parents must take the time to equip religious knowledge in children properly